2009
DOI: 10.1111/j.1540-8175.2008.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Atrial Appendage Functions According to Different Etiologies of Atrial Fibrillation with a Tissue Doppler Imaging Technique by Using Transesophageal Echocardiography

Abstract: LAA function deteriorated most severely in mitral stenosis and least in hyperthyroidism. The LAA area change and PW-Doppler emptying velocity were important predictors for SEC or thrombi. Although TDI was not superior to classical methods, it provided complementary data to PW-Doppler velocities for predicting SEC and thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
2
13
0
1
Order By: Relevance
“…[11][12][13][14][15][16] Transesophageal TDE patterns of LAA were reproducible and similar to those of Doppler flow, and peak TDE velocities correlated well with flow velocity and the LAA functions were evaluated in the patients with mitral stenosis or atrial fibrillation. [11][12][13][14][15][16] Recently, Uret-sky et al demonstrated that transthoracic TDE could be used to analyze LAA function and detect decreased LAA wall velocity in patients with atrial fibrillation. 8 In the present study, including patients who underwent TEE, we showed transthoracic TDE of the LAA wall velocities had significant correlations with transesophageal Doppler flow velocities in the LAA.…”
Section: Discussion: Analysis Of Laa Function By Transthoracic Echocamentioning
confidence: 87%
See 1 more Smart Citation
“…[11][12][13][14][15][16] Transesophageal TDE patterns of LAA were reproducible and similar to those of Doppler flow, and peak TDE velocities correlated well with flow velocity and the LAA functions were evaluated in the patients with mitral stenosis or atrial fibrillation. [11][12][13][14][15][16] Recently, Uret-sky et al demonstrated that transthoracic TDE could be used to analyze LAA function and detect decreased LAA wall velocity in patients with atrial fibrillation. 8 In the present study, including patients who underwent TEE, we showed transthoracic TDE of the LAA wall velocities had significant correlations with transesophageal Doppler flow velocities in the LAA.…”
Section: Discussion: Analysis Of Laa Function By Transthoracic Echocamentioning
confidence: 87%
“…The usefulness of transesophageal TDE for the assessment of LAA function has been well described 11–16 . Transesophageal TDE patterns of LAA were reproducible and similar to those of Doppler flow, and peak TDE velocities correlated well with flow velocity and the LAA functions were evaluated in the patients with mitral stenosis or atrial fibrillation 11–16 . Recently, Uretsky et al demonstrated that transthoracic TDE could be used to analyze LAA function and detect decreased LAA wall velocity in patients with atrial fibrillation 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also implicated that the modification of the AVD does not influence filling pattern in patients with normal ventricular function. 15,[20][21][22] In this study, we used LAAEV and LSV for evaluation of LAA function. 9,16,19 Both LA and LAA is potential site for development of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…3). Furthermore, TEE with TDI is useful for risk stratification and provides additional prognostic information over conventional impulse-wave Doppler parameters [43,44]. Contrast TDI contributes to better visualisation of LAA, improving our understanding of its structure and function, assessment of SEC, and thromboembolic risk [6,45].…”
Section: Blood Flow Patterns and Risk Stratificationmentioning
confidence: 99%